New skull remains of Phorusrhacos longissimus (Aves, Cariamiformes) from the Miocene of Argentina: implications for the morphology of Phorusrhacidae. (November 2019) - Degrange, Federico J.; Eddy, Drew; Puerta, Pablo; Clarke, Julia
Abstract: The giant carnivorous phorusrhacid bird Phorusrhacos longissimus (Aves, Cariamiformes) was first described in 1887 by Florentino Ameghino on the basis of a jaw fragment. The majority of a skull of the species still encased in crumbling rock was preserved only long enough for illustrations to be made by Carlos Ameghino in the field and for a brief description to be written. Skull remains of this species have remained scarce, and few postcranial remains have been figured. Here, we reassess the cranial anatomy of this outstanding 'terror bird' species taking into account data from a newly discovered skull. An additional specimen of a well-preserved dorsal vertebra referable to Phorusrhacinae is also described from a separate locality within the Miocene Santa Cruz Formation (late early Miocene) from Santa Cruz Province in Argentina. The skull includes most of the rostrum, skull roof, and mandible and is compared with material from other members of the Phorusrhacinae. The new data from the skull and vertebra provide morphological features of this clade that benefit future taxonomic and phylogenetic analyses of this iconic group of birds.